Semi-solid battery and method of manufacturing the same

CN123018066APending Publication Date: 2026-10-30BEIJING CHEHEJIA AUTOMOBILE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511686632.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-17
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

[0015]本申请将固态电解质层设置在极片表面上,保证了固态电解质和极片上的活性材料紧密有效接触,这样既可以改善因为直接使用固态电解质膜导致的界面接触差的问题,又提供了有效的锂离子传输通路,因此兼顾了长寿命和倍率性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018066A_ABST
    Figure CN123018066A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of batteries, in particular to a semi-solid battery and a preparation method thereof. The semi-solid battery comprises a positive electrode sheet, a negative electrode sheet and a solid electrolyte layer arranged on the surface of at least one electrode sheet; the surface density of the solid electrolyte layer accounts for 10-40% of the surface density of the electrode sheet; the thickness of the solid electrolyte layer is 3-30 microns; and the raw material of the solid electrolyte layer comprises a solid electrolyte. The solid electrolyte layer is arranged on the surface of the electrode sheet, so that the solid electrolyte and the active material on the electrode sheet are in close and effective contact, which can improve the poor interface contact caused by directly using the solid electrolyte film, and provide an effective lithium ion transmission path, so that the long service life and the rate performance are considered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, specifically to a semi-solid-state battery and its preparation method. Background Technology

[0002] With the development of the battery industry, lithium-ion batteries are used in various fields. Traditional lithium-ion batteries use flammable organic solutions as electrolytes, which makes it difficult to further improve battery quality and energy, and also poses safety hazards.

[0003] To address these technical issues, the common approach is to replace liquid electrolytes with solid electrolytes. However, solid electrolytes cannot achieve efficient lithium-ion transport with electrode active materials during charging and discharging, thus affecting battery performance. Summary of the Invention

[0004] This application provides a semi-solid battery and its preparation method, which solves the problem that solid electrolytes cannot achieve efficient lithium-ion transport with electrode active materials during charging and discharging.

[0005] To address the aforementioned technical problems, this application provides a semi-solid-state battery, comprising: a positive electrode, a negative electrode, and a solid electrolyte layer disposed on the surface of at least one electrode; wherein the areal density of the solid electrolyte layer accounts for 10-40% of the areal density of the electrode; the thickness of the solid electrolyte layer is 3-30 μm; and the raw material of the solid electrolyte layer includes a solid electrolyte.

[0006] In one embodiment, the solid electrolyte includes at least one of the following: oxide solid electrolyte, sulfide solid electrolyte, halide solid electrolyte, nitride solid electrolyte, and hydride solid electrolyte.

[0007] In one embodiment, the oxide solid electrolyte has a structural formula including at least one of the following: Li (1+x1) Q x1 M (2-x1) (PO4)3, Li (7-x2) La3Zr (2-x2) A x2 O 12 Li 3×x3 B (2 / 3-x3) CO3, Li (3+x4) D y E (1-y) F (4-z) G zWherein, 0≤x1<1, Q includes at least one of Al, Cr, Ba, Fe, Sc, In, Lu, Y, and La, M includes at least one of Fe, Co, Gr, and Mn, 0≤x2<1, A includes at least one of Sb, Nb, Ta, Te, and W, 0.04<x3<0.17, B includes at least one of La, Sr, Ba, and Nd, C includes at least one of Al, Ti, and Ge, -1<x4<2, 0≤y≤1, 0≤z≤2, D includes at least one of B, Al, In, Si, Ge, Sn, Ti, W, and Mo, E includes at least one of P, As, Sb, and Bi, F includes at least one of S and Se, and G includes at least one of F, Cl, Br, and I.

[0008] In one embodiment, the sulfide solid electrolyte has a structural formula including at least one of the following: Li6PS5Cl, Li3PS4, Li2S-P2S5, Li2S-GeS2, Li2S-SiS2, Li2S-LS2-P2S5; wherein, L includes at least one of Si, Ge, Sn, and Al.

[0009] In one embodiment, the halide solid electrolyte has the structural formula Li x5 M1 a M2 b M3 c M4 d M5 e Wherein, 1≤x5≤4, 0≤a≤1, 0≤b≤1, 0≤c≤1, 0≤d≤1, 3≤e≤6, M1 includes at least one of B, Al, Ga, In, Sc, Y, La, Ce, Lu, Yb, Ho, Er, Tb, and Dy; M2 includes at least one of Si, Ge, Sn, Ti, Zr, and Hf; M3 includes at least one of V, Nb, and Ta; M4 includes at least one of O and S; and M5 includes at least one of F, Cl, Br, and I.

[0010] In one embodiment, the nitride solid electrolyte has a structural formula including at least one of the following: Li3N, Li x6 PO f N g Where 0 < x6 ≤ 1, 0 < f ≤ 1, 0 < g ≤ 1.

[0011] In one embodiment, the hydride solid electrolyte has the structural formula LiBH4.

[0012] In one embodiment, the solid electrolyte layer raw material further includes a binder; wherein the solid electrolyte and the binder account for 70-99 wt% and 0.5-10.5 wt% of the solid electrolyte layer raw material, respectively.

[0013] This application also provides a method for preparing a semi-solid battery, comprising: obtaining electrode material and solid electrolyte layer material; coating the solid electrolyte layer material onto at least one surface of the electrode material, and assembling a semi-solid battery based on the electrode material; wherein the areal density of the solid electrolyte layer accounts for 10-40% of the areal density of the electrode material; and the thickness of the solid electrolyte layer is 3-30 μm.

[0014] This application also provides an electrical device, which includes a semi-solid battery that provides electrical energy to the device.

[0015] This application places the solid electrolyte layer on the surface of the electrode, ensuring close and effective contact between the solid electrolyte and the active material on the electrode. This not only improves the problem of poor interface contact caused by directly using the solid electrolyte membrane, but also provides an effective lithium-ion transport pathway, thus achieving both long lifespan and rate performance. Attached Figure Description

[0016] Figure 1 This is a flowchart illustrating a method for preparing a semi-solid-state battery as provided in an embodiment of this application. Figure 2 This is a structural diagram of a positive electrode layer and a negative electrode layer both coated with solid electrolyte raw materials, provided in the embodiments of this application; Figure 3 This is a structural diagram of a method in which a solid electrolyte material is coated only on the surface of the positive electrode layer, as provided in an embodiment of this application. Figure 4 This is a structural diagram of a method in which a solid electrolyte material is coated only on the surface of the negative electrode layer, as provided in an embodiment of this application. Detailed Implementation

[0017] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.

[0018] The terms "first" and "second" in the specification and claims of this application may explicitly or implicitly include one or more of the features. In the description of this application, unless otherwise stated, "multiple" means two or more. Furthermore, "and / or" in the specification and claims indicates at least one of the connected objects, and the character " / " generally indicates that the preceding and following objects are in an "or" relationship.

[0019] This application provides a semi-solid battery, which includes: a positive electrode, a negative electrode, and a solid electrolyte layer disposed on the surface of at least one electrode.

[0020] In this embodiment, the solid electrolyte layer is placed on the surface of the electrode, which ensures close and effective contact between the solid electrolyte and the active material on the electrode. This not only improves the problem of poor interface contact caused by directly using the solid electrolyte membrane, but also provides an effective lithium-ion transport pathway, thus taking into account both long lifespan and rate performance.

[0021] The areal density of the solid electrolyte layer accounts for 10-40% of the areal density of the electrode sheet; the thickness of the solid electrolyte layer is 3-30 μm; and the raw material of the solid electrolyte layer includes solid electrolyte.

[0022] In this embodiment, the areal density of the solid electrolyte layer is set to be 10-40% of the areal density of the electrode, and the thickness of the solid electrolyte layer is set to be 3-30 μm. These are all limitations on the thickness of the solid electrolyte layer and the electrode. If the areal density of the solid electrolyte layer is less than 10% of the areal density of the electrode, or the thickness of the solid electrolyte layer is less than 3 μm, the processing consistency cannot be met and it is easy to break and short-circuit. If the areal density of the solid electrolyte layer is greater than 40% of the areal density of the electrode, or the thickness of the solid electrolyte layer is greater than 30 μm, the resistance will be too high and there will be no advantage in specific energy because the solid electrolyte layer is too thick.

[0023] Specifically, the areal density of the solid electrolyte layer accounts for 10%, 20%, 30%, 40% of the areal density of the electrode sheet or any value within the above range; the thickness of the solid electrolyte layer is 3μm, 10μm, 15μm, 20μm, 25μm, 30μm or any value within the above range.

[0024] Among them, the structural formula of the oxide solid electrolyte in the solid electrolyte includes at least one of the following: Li (1+x1) Q x1 M (2-x1) (PO4)3, Li (7-x2) La3Zr (2-x2) A x2 O 12 Li 3×x3 B (2 / 3-x3) CO3, Li (3+x4) D y E (1-y) F (4-z) G zWherein, 0≤x1<1, Q includes at least one of Al, Cr, Ba, Fe, Sc, In, Lu, Y, and La, M includes at least one of Fe, Co, Gr, and Mn, 0≤x2<1, A includes at least one of Sb, Nb, Ta, Te, and W, 0.04<x3<0.17, B includes at least one of La, Sr, Ba, and Nd, C includes at least one of Al, Ti, and Ge, -1<x4<2, 0≤y≤1, 0≤z≤2, D includes at least one of B, Al, In, Si, Ge, Sn, Ti, W, and Mo, E includes at least one of P, As, Sb, and Bi, F includes at least one of S and Se, and G includes at least one of F, Cl, Br, and I.

[0025] The core characteristic of oxide solid electrolytes is that anions are in the form of O 2- The above materials are mainly composed of oxygen ions and cations (such as P). 5+ Zr 4+ La 3+ The formation of a stable oxide framework ensures the material remains stable over a wide temperature range and in complex chemical environments, making it less prone to decomposition or phase transition. Simultaneously, the regular gaps or vacancies between the oxygen ion framework provide dedicated migration pathways for lithium ions. Furthermore, the chemical inertness of the oxide framework gives it a wide electrochemical window, allowing it to be matched with high-voltage cathode materials and avoid redox side reactions.

[0026] Among them, the structural formula of the sulfide solid electrolyte in the solid electrolyte includes at least one of the following: Li6PS5Cl, Li3PS4, Li2S-P2S5, Li2S-GeS2, Li2S-SiS2, Li2S-LS2-P2S5; wherein L includes at least one of Si, Ge, Sn, and Al.

[0027] Sulfide solid electrolytes are essentially solid lithium-ion conductors containing sulfur elements. The framework of the above materials consists of metal cations (P... 5+ 、Ge 4+ Si 4+ (etc.) and S 2- Formed through covalent or ionic bonds. Furthermore, all of the above materials contain a large amount of Li. + And Li + It does not participate in strong binding of the backbone, but only acts as a charge balancing ion or fills the gaps in the backbone. It has the ability to migrate from one site to another, which is the core function of electrolyte conduction ions.

[0028] Among them, the structural formula of the halide solid electrolyte in the solid electrolyte is Li x5 M1 a M2 b M3 c M4d M5 e Wherein, 1≤x5≤4, 0≤a≤1, 0≤b≤1, 0≤c≤1, 0≤d≤1, 3≤e≤6, M1 includes at least one of B, Al, Ga, In, Sc, Y, La, Ce, Lu, Yb, Ho, Er, Tb, and Dy; M2 includes at least one of Si, Ge, Sn, Ti, Zr, and Hf; M3 includes at least one of V, Nb, and Ta; M4 includes at least one of O and S; and M5 includes at least one of F, Cl, Br, and I.

[0029] The basic structure of halide solid electrolytes consists of halogen and metallic elements. Halogen anions have a larger radius and interact weaker with lithium ions than divalent sulfur or oxygen anions, which is beneficial for the rapid transport of lithium ions. Moreover, due to their high electronegativity, halide ions in this material have a strong ability to bind electrons and are not easily oxidized, giving the material a wide electrochemical window. This allows for better compatibility with high-voltage cathode materials and enables stable cycling under high voltage conditions.

[0030] Among them, the structural formula of nitride solid electrolytes includes at least one of the following: Li3N, Li x6 PO f N g Where 0 < x6 ≤ 1, 0 < f ≤ 1, 0 < g ≤ 1.

[0031] Li3N, Li x6 PO f N g With nitrogen ions as the key anion, whose ionic radius lies between that of oxygen and sulfide ions and whose electronegativity is lower than that of oxygen ions, the nitride framework is naturally well-suited to Li. + migrate.

[0032] Among them, the structural formula of the hydride solid electrolyte in the solid electrolyte is LiBH4.

[0033] LiBH4 uses hydride anions as its key anion and has two crystal phases (low-temperature phase and high-temperature phase). Through simple temperature control, it can transition from an insulating state to a highly conductive state, and this phase transition is reversible, providing a flexible control method for applications in the mid-temperature range. Furthermore, LiBH4 possesses unique advantages of low migration barriers and high ionic conductivity.

[0034] The solid electrolyte layer raw materials also include: binder; the solid electrolyte and binder account for 70~99wt% and 0.5~10.5wt% of the solid electrolyte layer raw materials, respectively.

[0035] Because the non-flowability and brittleness of solid systems prevent them from independently achieving interfacial contact, structural stability, and processing, adhesives can solve these problems and also provide an auxiliary pathway for ion conduction. However, since the ionic conductivity of adhesives is usually lower than that of solid electrolytes, their addition amount cannot be too large to avoid a decrease in overall conductivity due to excessive adhesive.

[0036] Specifically, the solid electrolyte accounts for 70 wt%, 75 wt%, 80 wt%, 85 wt%, 90 wt%, 95 wt%, 99 wt% of the solid electrolyte layer raw material or any value within the above range; the binder accounts for 0.5 wt%, 5 wt%, 7 wt%, 9 wt%, 10 wt% of the solid electrolyte layer raw material or any value within the above range.

[0037] The adhesive can be selected from one or more of polyvinylidene fluoride, carboxylated styrene-butadiene latex, styrene-butadiene rubber, polyvinyl alcohol, sodium carboxymethyl cellulose, and polytetrafluoroethylene.

[0038] These molecular structures contain polar groups or flexible segments, which can bind to the surface of the substrate through van der Waals forces, hydrogen bonds, or mechanical intercalation. Furthermore, they are not easily decomposed or reacted in normal operating environments, exhibiting good chemical stability. In addition, they can all form a uniform slurry through dissolution or emulsion dispersion, resulting in a continuous film after coating, encapsulating and connecting dispersed particles into a whole, demonstrating good film-forming properties and continuity.

[0039] This application also provides a method for preparing a semi-solid-state battery, such as... Figure 1 As shown, it includes: S1. Obtain raw materials for electrode sheets and solid electrolyte layers; S2. Apply solid electrolyte layer material to at least one surface of the electrode and assemble a semi-solid battery based on the electrode.

[0040] This method allows for the simple and rapid direct coating of solid electrolyte materials onto the surface of an electrode, thereby obtaining a semi-solid-state battery based on the electrode.

[0041] S1 specifically includes: mixing and stirring a positive or negative active material, a conductive agent, a binder, and a solvent to obtain a positive or negative material, and obtaining a positive or negative electrode sheet based on the positive or negative material; mixing and stirring a solid electrolyte, a binder, and a solvent to obtain a solid electrolyte layer raw material.

[0042] Among them, the positive electrode active material includes one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, nickel-cobalt-manganese ternary materials, and nickel-cobalt-aluminum ternary materials.

[0043] Li in lithium cobalt oxide + Co³+ O² - Hexagonal close packing, Li + Within the octahedral interstices between the CoO2 layers, a layered structure of alternating Li-CoO2-Li layers is formed. During charging, Li... + It can be extracted from the interlayer gap, and Li can be discharged during discharge. + During the re-intercalation and deintercalation process, only a slight change in the interlayer spacing occurs in the crystal structure, ensuring cycle stability.

[0044] O² in lithium manganese oxide - It exhibits face-centered cubic close packing, Li + Located in the tetrahedral interstitium, Mn³ + / Mn 4+ Located in the octahedral interstices, it forms a three-dimensional open lithium-ion migration channel. Li + It can be quickly de-embedded in three-dimensional channels with low migration resistance and excellent rate performance.

[0045] PO4 in lithium iron phosphate 3- The tetrahedrons and FeO6 octahedrons are connected by sharing vertices, forming a rigid three-dimensional framework. (Li) + Located in a one-dimensional channel. Li + It can only be inserted and removed along one-dimensional channels, and its migration rate is lower than that of spinel and layered materials, but PO4 3- The rigid framework makes the structure extremely stable, even for Li + It completely separates, and the change in crystal volume is very small, with no risk of structural collapse during cycling.

[0046] Mn² in lithium manganese iron phosphate + with Fe² + With a radius close to that of lithium iron phosphate, it can completely replace some of the Fe²⁺ in lithium iron phosphate. + A homogeneous solid solution is formed, maintaining the olivine crystal structure and a rigid framework. The introduction of Mn does not disrupt the one-dimensional Li. + Channel, but Mn² + The presence of Li slightly widened the channel. + The migration rate is slightly higher than that of pure lithium iron phosphate; meanwhile, Mn² + / Mn³ + Its redox potential is higher than that of Fe² + / Fe³ + This causes the material to exhibit a dual voltage plateau.

[0047] Nickel-cobalt-manganese ternary materials exhibit a layered structure with alternating Li-(Ni / Co / Mn)O2-Li layers, but Ni 2+ Co³ + Mn 4+They collectively occupy transition metal sites. The introduction of Ni provides the main capacity contribution, Co stabilizes the layered structure, and Mn enhances safety. The three work together to achieve high capacity and stable conduction.

[0048] In nickel-cobalt-aluminum ternary materials, Al³ + Replacement of Mn 4+ Occupying transition metal sites, Al 3+ The ionic radius of Co³ + Closer proximity results in a more compact layered structure. Al³ + It possesses stronger ionic bonding forces, which can suppress excessive expansion of interlayer spacing during charging and improve structural stability.

[0049] The negative electrode active material includes one or more of the following: artificial graphite, natural graphite, mesophase carbon microspheres, soft carbon, hard carbon, elemental silicon, silicon oxide, silicon-carbon composite, and lithium titanate.

[0050] All of the above-mentioned negative electrode active materials can achieve Li + Reversible migration and storage during charging and discharging, while meeting requirements such as high capacity, stable cycling, and low potential.

[0051] The solvent is selected from one or more of the following: water, ethanol, N-methylpyrrolidone (NMP), acetone, acetonitrile, toluene, xylene, anisole, heptane, decane, ethyl acetate, ethyl propionate, and butyl butyrate.

[0052] Solvents disperse solute particles into tiny units at the molecular or ionic level by breaking the intermolecular forces (such as ionic bonds, hydrogen bonds, and van der Waals forces), forming a homogeneous and stable solution. Therefore, this solvent is a substance with good solubility based on the polarity selection of substances such as positive electrode active materials, negative electrode active materials, binders, and solid electrolytes.

[0053] The conductive agent is selected from one or more of conductive carbon black, graphite, graphene, and carbon nanotubes.

[0054] The aforementioned conductive materials all possess high conductivity, excellent dispersibility, and stable chemical properties. Furthermore, through unique microstructures (such as nanoscale particles, layered or tubular morphologies), they construct highly efficient conductive networks in electrode and other applications, further enhancing their conductivity.

[0055] The positive or negative active material, conductive agent, and binder account for 70-99 wt%, 0.5-4.5 wt%, and 0.5-5.5 wt% of the positive or negative active material, respectively.

[0056] This mass ratio is to obtain a more stable positive or negative electrode material solution, while ensuring the respective functions of the electrode active material, conductive agent, and binder.

[0057] Specifically, the positive or negative active material accounts for 70, 80, 90, 99 wt% of the positive or negative electrode material or any value within the above range; the conductive agent accounts for 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5 wt% of the positive or negative electrode material or any value within the above range; and the binder accounts for 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5 wt% of the positive or negative electrode material or any value within the above range.

[0058] Among them, the solid electrolyte and binder account for 70~99wt% and 0.5~10.5wt% of the mass fraction of the solid electrolyte layer raw material, respectively.

[0059] Because the non-flowability and brittleness of solid systems prevent them from independently achieving interfacial contact, structural stability, and processing, adhesives can solve these problems and also provide an auxiliary pathway for ion conduction. However, since the ionic conductivity of adhesives is usually lower than that of solid electrolytes, their addition amount cannot be too large to avoid a decrease in overall conductivity due to excessive adhesive.

[0060] Specifically, the solid electrolyte accounts for 70, 75, 80, 85, 90, 95, or 99 wt% of the solid electrolyte layer raw material, or any value within the above range; the binder accounts for 0.5, 3, 5, 7, 9, or 10 wt% of the solid electrolyte layer raw material, or any value within the above range.

[0061] S2 specifically includes: coating solid electrolyte raw materials onto the surface of at least one substrate, including a positive electrode (or positive electrode layer) and a negative electrode (or negative electrode layer), using a double-layer coating method (e.g., an active material layer and a solid electrolyte layer are sequentially disposed on one surface of the substrate), obtaining a dry cell based on the electrode, and finally obtaining a semi-solid battery after injecting electrolyte. Among these, Figure 2 This is a structural diagram showing that both the positive and negative electrode layers are coated with solid electrolyte raw materials. Figure 3 This is a structural diagram showing the coating of solid electrolyte material only on the surface of the positive electrode layer; Figure 4 This is a structural diagram showing that solid electrolyte raw materials are coated only on the surface of the negative electrode layer.

[0062] Specifically, the electrolyte includes at least one of conventional carbonate-based and ether-based electrolytes.

[0063] This application also provides an electrical device, which includes a semi-solid battery that provides electrical energy to the device.

[0064] To better explain this solution, embodiments and comparative examples are also provided below.

[0065] Example 1 1. Mix 70wt% of positive electrode active material lithium cobalt oxide and 70wt% of negative electrode active material artificial graphite with 0.5wt% of conductive agent carbon black and 0.5wt% of binder polyvinylidene fluoride to prepare positive and negative electrode slurries, and obtain corresponding positive and negative electrode sheets based on the positive and negative electrode slurries.

[0066] 2. Add 70wt% solid electrolyte Li 1.5 Q 0.5 Mn 1.5 (PO4)3 and 0.5 wt% of the binder polyvinylidene fluoride were mixed and stirred in a certain proportion to obtain a solid electrolyte slurry.

[0067] 3. A double-layer coating method is used to coat the solid electrolyte slurry onto the outer layers of the positive and negative electrodes, and the areal density of the solid electrolyte layer accounts for 10% of the areal density of the electrode sheet.

[0068] 4. Roll the composite negative electrode sheet and positive electrode sheet together to form a JR, then hot press it at 50 MPa and 150℃ for 10 minutes to obtain a dry cell, and then obtain a semi-solid battery by injecting electrolyte.

[0069] Example 2-11 The steps are the same as in Example 1, except for the parameters or parameter content, as detailed in Table 1.

[0070] Table 1. Parameters or parameter content in the embodiments.

[0071] Comparative Example 1 1. Mix 70wt% of positive electrode active material lithium cobalt oxide and 70wt% of negative electrode active material artificial graphite with 0.5wt% of conductive agent carbon black and 0.5wt% of binder polyvinylidene fluoride to prepare positive and negative electrode slurries.

[0072] 2. The positive and negative electrode pastes are coated onto the substrate to obtain positive and negative electrode sheets.

[0073] 3. Roll the composite negative electrode sheet and positive electrode sheet together to form a JR, then hot press it at 50 MPa and 150℃ for 10 minutes to obtain a dry cell, and then inject electrolyte to obtain a battery.

[0074] The batteries in the above embodiments and comparative examples were charged and discharged at a rate of 0.33C, and the test data are shown in Table 2.

[0075] Table 2 Battery Test Data

[0076] As can be seen from the data in Table 2, compared with the example, the example has a tighter interface and compatibility, less lithium loss due to side reactions, and better kinetics, so it achieves higher capacity utilization.

[0077] Finally, it should be noted that in this application, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes the aforementioned element.

[0078] The above description, in conjunction with specific embodiments, provides a further detailed explanation of this application and should not be construed as limiting the specific implementation of this application to these descriptions. Those skilled in the art to which this application pertains can make several simple deductions or substitutions without departing from the concept of this application.

Claims

1. A semi-solid-state battery, characterized in that, The semi-solid battery includes: a positive electrode, a negative electrode, and a solid electrolyte layer disposed on the surface of at least one electrode; The areal density of the solid electrolyte layer accounts for 10-40% of the areal density of the electrode sheet; the thickness of the solid electrolyte layer is 3-30 μm; and the raw material of the solid electrolyte layer includes a solid electrolyte.

2. The semi-solid-state battery according to claim 1, characterized in that, The solid electrolyte includes at least one of the following: oxide solid electrolyte, sulfide solid electrolyte, halide solid electrolyte, nitride solid electrolyte, and hydride solid electrolyte.

3. The semi-solid-state battery according to claim 2, characterized in that, The structure of the oxide solid electrolyte includes at least one of the following: Li (1+x1) Q x1 M (2-x1) (PO4)3, Li (7-x2) La3Zr (2-x2) A x2 O 12 Li 3×x3 B (2 / 3-x3) CO3, Li (3+x4) D y E (1-y) F (4-z) G z ; Wherein, 0≤x1<1, Q includes at least one of Al, Cr, Ba, Fe, Sc, In, Lu, Y, and La, M includes at least one of Fe, Co, Gr, and Mn, 0≤x2<1, A includes at least one of Sb, Nb, Ta, Te, and W, 0.04<x3<0.17, B includes at least one of La, Sr, Ba, and Nd, C includes at least one of Al, Ti, and Ge, -1<x4<2, 0≤y≤1, 0≤z≤2, D includes at least one of B, Al, In, Si, Ge, Sn, Ti, W, and Mo, E includes at least one of P, As, Sb, and Bi, F includes at least one of S and Se, and G includes at least one of F, Cl, Br, and I.

4. The semi-solid-state battery according to claim 2, characterized in that, The sulfide solid electrolyte has a structural formula including at least one of the following: Li6PS5Cl, Li3PS4, Li2S-P2S5, Li2S-GeS2, Li2S-SiS2, Li2S-LS2-P2S5; Wherein, L includes at least one of Si, Ge, Sn, and Al.

5. The semi-solid-state battery according to claim 2, characterized in that, The structural formula of the halide solid electrolyte is Li x5 M1 a M2 b M3 c M4 d M5 e ; Wherein, 1≤x5≤4, 0≤a≤1, 0≤b≤1, 0≤c≤1, 0≤d≤1, 3≤e≤6, M1 includes at least one of B, Al, Ga, In, Sc, Y, La, Ce, Lu, Yb, Ho, Er, Tb, and Dy; M2 includes at least one of Si, Ge, Sn, Ti, Zr, and Hf; M3 includes at least one of V, Nb, and Ta; M4 includes at least one of O and S; and M5 includes at least one of F, Cl, Br, and I.

6. The semi-solid-state battery according to claim 2, characterized in that, The nitride solid electrolyte has a structural formula including at least one of the following: Li3N, Li x6 PO f N g ; Where 0 < x6 ≤ 1, 0 < f ≤ 1, 0 < g ≤ 1.

7. The semi-solid-state battery according to claim 2, characterized in that, The structural formula of the hydride solid electrolyte is LiBH4.

8. The semi-solid-state battery according to claim 1, characterized in that, The raw material for the solid electrolyte layer also includes: a binder; The solid electrolyte and the binder account for 70-99 wt% and 0.5-10.5 wt% of the raw materials of the solid electrolyte layer, respectively.

9. A method for preparing a semi-solid-state battery, characterized in that, include: Obtain raw materials for electrode sheets and solid electrolyte layers; The solid electrolyte layer material is coated onto at least one surface of the electrode, and a semi-solid battery is obtained by assembling based on the electrode. The areal density of the solid electrolyte layer accounts for 10-40% of the areal density of the electrode sheet; the thickness of the solid electrolyte layer is 3-30 μm.

10. An electrical appliance, characterized in that, The electrical device includes a semi-solid-state battery as described in any one of claims 1-8, wherein the semi-solid-state battery provides electrical energy to the electrical device.